Transhumanism and Evolution. Considerations on Darwin, Lamarck and Transhumanism - Bardziński, Filip (ETHICS IN PROGRESS, 2014)
In the paper, I discuss the possible gap between the transhumanist perspective of controlling and perfecting human evolution through scientific means and the Darwinian and neo-Darwinian theory of biological evolution. I argue that, due to such gap, the transhumanist programme is flawed and requires a new and better understanding of biological mechanisms in order to attain its goals.